Methods for improving print quality for konica minolta 6085 digital printing press - Vovk, O. V.; Chebotarova, I. B.; Donskiy, D. O.; Chebotarov, R. I. (ХНУРЕ, 2025)
The paper examines the use of different raster structures with different dot shapes, taking into account the typical recommendations of printing press manufacturers and the features of the Konica Minolta 6085 printing press to improve the quality of printed products. The use of various rasterization technologies allows solving not only the classic problems of moir formation, graininess, improving the smoothness of halftone printing, etc., but also more specific problems. The use of different forms of raster dots in digital printing can be used to expand the color gamut; the combination of stochastic rasterization, different forms of dots and high-precision line screen allows you to simulate various printing processes and make better quality color proofs. Based on the results of the evaluation, recommendations were developed for the selection of types of rasters according to the types of originals and materials.
Keywords: digital printing; assessment; stochastic; raster; rasterization; line screen